Al-Biruni’s Enduring Contributions to Cartographic Science - Ahn, Young-Jin; Juraev, Zuhriddin (Journal for Geography, 2024)
This paper commemorates the 1050th anniversary of Abu Rayhan Al-Biruni and delves into his unparalleled contributions to the geosciences and cartography within the context of the Islamic Golden Age. Al-Biruni’s work, characterized by its interdisciplinary approach and meticulous methodology, has not only advanced the field of geography but also connected diverse cultural perspectives. By examining Al-Biruni’s groundbreaking contributions, this study highlights his innovative methods for measuring the Earth’s radius, his unique cartographic representations, and his synthesis of knowledge from various civilizations. Focusing on Al-Biruni’s contributions from both a geographical and educational perspective, we illuminate his timeless impact on the discipline and provide insights that are of central importance to contemporary geography researchers and educators. This study underscores the importance of integrating Al-Biruni’s interdisciplinary methods, critical thinking, and cross-cultural analyses into modern geographical education, thereby enriching the academic exploration of geography and fostering a deeper appreciation for the interconnectedness of global cultures and scientific advancements.